Role of Maternal and Child Health Handbook on Improving Maternal, Newborn, and Child Health Outcomes: A Systematic Review and Meta-Analysis - Etsuko Nishimura; Md Obaidur Rahman; Erika Ota; Noriko Toyama; Yasuhide Nakamura (MDPI AG, 2023)
The objective of this review is to assess and synthesize the role of the maternal and child health (MCH) handbook on improving healthcare service utilization, behavior change, and health outcomes for women and children. A systematic search of all relevant existing reports was conducted on 14 January 2021, using the following online bibliographic databases: PubMed, EMBASE, MEDLINE, The Cochrane Library, Academic Search Premier, Emcare, APA PsycINFO, and Web of Science. Two reviewers independently performed study selection, data extraction, and quality assessment. We included 7 trials from 1430 articles, and a total of 2643 women. As overall risk of bias assessment, most domains of the Cochrane risk-of-bias assessment tool showed a high or unclear risk of bias. The risk of ≥6 antenatal care (ANC) visits was 19% higher (RR 1.19, 95% CI 1.09 to 1.30, I2 = 47%, 2 studies, 955 women, moderate certainty of evidence) and skilled birth attendants during delivery was 13% higher (RR 1.13, 95% CI 1.04 to 1.24, I2 = 0%, 2 studies, 1094 women, low certainty of the evidence) in the intervention group than in the control group. The MCH handbook can increase maternal health service utilization and early breastfeeding practice. It also leads to a sense of autonomy during ANC, better communication with healthcare providers, and support from family members.